The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s11524-006-9141-7
|View full text |Cite
|
Sign up to set email alerts
|

The Sociobiologic Integrative Model (SBIM): Enhancing the Integration of Sociobehavioral, Environmental, and Biomolecular Knowledge in Urban Health and Disparities Research

Abstract: Disentangling the myriad determinants of disease, within the context of urban health or health disparities, requires a transdisciplinary approach. Transdisciplinary approaches draw on concepts from multiple scientific disciplines to develop a novel, integrated perspective from which to conduct scientific investigation. Most historic and contemporary conceptual models of health were derived either from the sociobehavioral sciences or the biomolecular sciences. Those models deriving from the sociobehavioral scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…26,[29][30][31] Although income was accounted for in this study, other sociodemographic inequalities and geographical variation among African Americans and whites may also play a role in confounding the survival discrepancies seen. 32,33 This study showed that African Americans did not receive equivalent interventions as frequently as their white counterparts (ie, decreased rates of radiotherapy and surgical resection). Various analyses have shown that African Americans tend to receive lower quality health care even after accounting for barriers to access, such as the lack of health insurance.…”
Section: Discussionmentioning
confidence: 94%
“…26,[29][30][31] Although income was accounted for in this study, other sociodemographic inequalities and geographical variation among African Americans and whites may also play a role in confounding the survival discrepancies seen. 32,33 This study showed that African Americans did not receive equivalent interventions as frequently as their white counterparts (ie, decreased rates of radiotherapy and surgical resection). Various analyses have shown that African Americans tend to receive lower quality health care even after accounting for barriers to access, such as the lack of health insurance.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, our Hispanic category represents a heterogeneous population in terms of genetic background, culture, and duration of U.S. residence. In general, race/ethnicity serves as a marker for other genetic, exposure, and lifestyle factors [41]. Although we conjectured that racial/ethnic differences in screening rates for cancers before and after transplantation could have contributed to variation in cancer risk, we do not have data on cancer screening practices among transplant candidates or recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Th is discrepancy in incidence may explain the absence of high-quality studies on ESCC in the Western world. Although tobacco use (and less so alcohol use) is more commonplace in these more endemic regions, there are several other factors, including genetic variations, socioeconomic disparities, dietary factors, and possibly infectious causes, that likely also contribute to the diff erences in incidence across countries ( 31 ).…”
Section: Discussionmentioning
confidence: 99%